(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: To understand and respond to community sport needs in regional Victoria (Australia) to prevent and respond to gender based violence (GBV). The research followed a developmental evaluation approach where the information gathered was used to support resource development and implementation in real-time. Methods: Data were collected through focus groups and semi-structured interviews with community sports clubs, community sports stakeholders, academic experts, and community health organisations. Topics discussed: • Needs of community sport clubs to prevent and respond to GBV. • Current context and resources available. • Stakeholders involved. All discussions were transcribed verbatim and analysed against key themes established with the aim of developing resources and a support structure for community sports clubs. Results: 1. A centralised support system GBV is fragmented with multiple stakeholders across sport and health involved in prevention and response. This complex environment made it difficult for community sports clubs to access relevant information. A support system was established using the Regional Sport Assembly (RSA) as the central point of contact for community sports clubs, supported by an online portal. The RSA staff were found not to have the knowledge or expertise to adequately respond to GBV and training was provided to the workforce. • An awareness campaign Community sports clubs and individuals within those clubs were on a spectrum of readiness to prevent and respond to GBV. There therefore needed to be a variety of resources and support developed to meet clubs where they were at on this spectrum (i.e. ready to not ready). In addition, some were not fully aware of what constituted GBV. An awareness campaign was developed and implemented. Conclusion: GBV is a complex and fragmented issue with multiple stakeholders across the sport and health sectors. By taking a partnership approach the strengths of each partner were used. The Regional Sport Assembly was used to connect and support community sports clubs, and the strengths of the health organisations were used to upskill the sport workforce and support the development of relevant resources for community sports clubs. Support/Funding Source: This study was funded by the Victorian State Government Preventing Violence Through Sport Grants Program.